The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/asi.23448
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary, national, and departmental contributions to the literature of library and information science, 2007–2012

Abstract: We investigate the contributions of particular disciplines, countries, and academic departments to the literature of library and information science (LIS) using data for the articles published in 31 journals from 2007 to 2012. In particular, we examine the contributions of authors outside the United States, the United Kingdom, and Canada; faculty in departments other than LIS; and practicing librarians. Worldwide, faculty in LIS departments account for 31% of the journal literature; librarians, 23%; computer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 77 publications
1
25
0
5
Order By: Relevance
“…In his work, based on an analysis of citations, he showed that the discipline that contributed most citations to the LIS area was "Computer sciences," followed by "Communication," "Education," and "Management sciences." In our case, of the 10 most productive keywords, we have been able to confirm that "Computer sciences" is the area with the most influence (Walters & Wilder, 2016). This is to be expected, because the predominance of the "digital phenomenon" has reached all fields of knowledge, including the LIS area.…”
Section: New Words Appearing In 2004 and Their Behavior In Subsequentsupporting
confidence: 68%
“…In his work, based on an analysis of citations, he showed that the discipline that contributed most citations to the LIS area was "Computer sciences," followed by "Communication," "Education," and "Management sciences." In our case, of the 10 most productive keywords, we have been able to confirm that "Computer sciences" is the area with the most influence (Walters & Wilder, 2016). This is to be expected, because the predominance of the "digital phenomenon" has reached all fields of knowledge, including the LIS area.…”
Section: New Words Appearing In 2004 and Their Behavior In Subsequentsupporting
confidence: 68%
“…In the light of these data, can we argue that EPI, a journal which explicitly carries the word "professional" in its name, is no longer a practice-oriented journal? Walters and Wilder (2016) establish a quantitative indicator to make this determination, which defines such publications as those to which librarians contribute at least 1.5 times the number of articles submitted by any other group of authors…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we refer to a significant volume of works that conduct in-depth analysis of authorship in LIS publications (Finlay et al 2013;Joswick, 1999;Schlögl and Stock, 2008;Walters and Wilder, 2016). The degree of collaboration revealed by co-authored papers and the coexistence of works from both communities in certain publications are good general indicators of the healthy relationship between academia and the professional world.…”
Section: Journal Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Walters and Wider (2015) analyzed the contributions of institutions, disciplines, and countries to LIS research based on the papers published in 31 LIS journals from 2007 to 2012. After categorizing authors into the nine groups (Librarian, LIS, Computer Science, Management, Communication, Other Social Sciences, Natural Sciences, Other Fields, Non-Academic) and journals into the six types (LIS Core, Practice-oriented, Information Processing & Management, Management-oriented, Informetrics, other), Walters and Wider cross-tabulated papers by author and journal categories and then ranked the disciplines, countries, and departments using the publication count.…”
Section: Literature Review Evaluative Bibliometric Studies In Lismentioning
confidence: 99%